Kinetics of Hg and Pb Removal in Aqueous Solution Using Coal Fly Ash Adsorbent - Eko Prasetyo Kuncoro; Mochammad Zakki Fahmi (IPTEK The Journal for Technology and Science, 2014)
Water pollution caused by heavy metals is a serious problem to environment. Hg and Pb are heavy metals having high toxicity level. Heavy metals treatment is necessary before releasing them to environment. The use of adsorption method is interesting because of its relatively simple operation. The development of adsorption is oriented to the use of industrial waste such as coal fly ash. The objective of this research is to investigate the kinetics aspect of Hg and Pb adsorption using coal fly ash. A series of a Hg and Pb adsorption experiment using coal fly ash with time variation was carried out. The results were plotted to pseudo first order kinetic and pseudo second order kinetic model. The conclusion obtained was that Hg and Pb adsorption kinetics followed pseudo second order kinetic model